1928
DOI: 10.3733/hilg.v03n11p275
|View full text |Cite
|
Sign up to set email alerts
|

Lettuce seed and its germination

Abstract: that it will germinate at higher temperatures with the coats removed than with the coats on. It was found that if seeds are soaked for a half hour the coats can be. separated into three distinct coverings. Removal of the outer two has no influence on the germination of seeds at high temperature but when the innermost is removed germination proceeds normally as shown in figure 23. This result suggested the desira.bility of making a study of the development and structure of these parts of the seed. J ones"? desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
1

Year Published

1960
1960
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 2 publications
2
43
1
Order By: Relevance
“…The type of inhibition by solutions described above will be called "dark-osmotic inhibition" because firstly, the suppression of germination by solute correlates well with the osmotic pressure of the solution; secondly, the solute inhibition has little or no relation to the nature of the solute; and thirdly, at osmotic pressures lower than 5 atmospheres, the solutions do (4) found that the lettuce variety New York which normally does not germinate at 300 C will germinate well at that temperature if it first receives a period of low temperature in the imbibed condition. Low temperature pretreatment, during which no seeds germinate, is also capable of negating dark-osmotic inhibition of Grand Rapids lettuce seeds at 210 C. Seeds were sown on 0.18 M mannitol and stored for varying periods in darkness at 5± 2°C.…”
Section: Effects Of Light Upon Solute Inhibition Inmentioning
confidence: 99%
See 2 more Smart Citations
“…The type of inhibition by solutions described above will be called "dark-osmotic inhibition" because firstly, the suppression of germination by solute correlates well with the osmotic pressure of the solution; secondly, the solute inhibition has little or no relation to the nature of the solute; and thirdly, at osmotic pressures lower than 5 atmospheres, the solutions do (4) found that the lettuce variety New York which normally does not germinate at 300 C will germinate well at that temperature if it first receives a period of low temperature in the imbibed condition. Low temperature pretreatment, during which no seeds germinate, is also capable of negating dark-osmotic inhibition of Grand Rapids lettuce seeds at 210 C. Seeds were sown on 0.18 M mannitol and stored for varying periods in darkness at 5± 2°C.…”
Section: Effects Of Light Upon Solute Inhibition Inmentioning
confidence: 99%
“…Frequently, when surgery has been performed on seeds, the cotyledons emerge before the rootlet, and root growth may be severely curtailed. Borthwick and Robbins (4) Dark-osmotic inhibitioni should noxx be ssufficiently w-ell understoo(l to be employed routinely as…”
Section: Seed Surgery and Dark-osmotic Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition of lettuce (Lactuca sativa L.) seed germination at higher temperatures (thermodormancy) has been attributed to several factors: (a) restraint of the embryo's growth by the endosperm (5), which causes the absence of over-all embryo expansion (10); (b) reduction of the permeability of the seed coats (endosperm and integumentary membrane) to oxygen and carbon dioxide (5,7); (c) accumulation of metabolic products in the endosperm or in the embryo which inhibit initial germination stages (5); (d) nonfunctioning of the active form of the phytochrome (21); (e) formation of a temperature dependent inhibitor during the initial germination stages (4); (f) inhibition of radicle growth (16); and (g) diffusion of a growth-inhibiting substance from the seed into the aqueous medium (22).…”
mentioning
confidence: 99%
“…Several treatments have been used to overcome thermodormancy in lettuce seeds: (a) removing all seed coverings (7); (b) subjecting the moist seed to low temperature to initiate germination (5); (c) exposing briefly to low temperature during the course of imbibition at higher temperature (4); (d) germinating seeds under an increased oxygen (5) or carbon dioxide (26) pressure; and (e) chemically treating with thiourea (25), kinetin (14), and humic acid (1 1). Ethylene has been reported to accelerate and stimulate the germination of certain seeds (27).…”
mentioning
confidence: 99%